A Case of Choroid Plexus Papilloma with Rare Location Presenting with Impaired Consciousness - Nurcan Ünal; Muhammet Mesut Nezir Engin; Önder Kılıçaslan; İbrahim Feyyaz Naldemir; Gülşen Yalçın; Uğur Avcı; Kenan Kocabay (İstanbul Medical Journal, 2019)

(untitled)
Intraventricular papillary neoplasms originating from the choroid plexus epithelium are called choroid plexus tumors (CPT). In pediatric patients. The most common findings in CPT are seizures, subarachnoid hemorrhage, focal neurological deficits, hydrocephalus and symptoms of increased intracranial pressure. A 4.5-month-old, previously healthy girl was admitted to our Pediatric Emergency Department with complaints of inadequate nutrition, vomiting and drowsiness in the last 2 days. The patient was admitted to the pediatric intensive care unit and saline loading treatment was initiated due to presumed dehydration caused by inadequate nutrition. As dehydration-related pathology was not detected, brain tomography scan was performed for possible cranial pathology and it revealed increased bilateral lateral ventricular diameters. As a result of magnetic resonance imaging results, the patient was diagnosed as having choroid plexus papilloma. After the shunt was inserted, the patient regained consciousness and an elective surgery was planned. Inadequate nutrition and drowsiness are the most common causes of admissions to pediatric emergency department, and these symptoms are usually due to dehydration. Cranial pathologies should be considered in patients who do not respond to fluid loading treatments and whose laboratory findings and vital signs are stable. As in our patient, the patients with choroid plexus papilloma should be evaluated clinically and shunt surgery should be performed firstly. Timing of surgery should be decided according to the effect and clinical status.